Effect of instructions prioritizing speed or accuracy on kinematics and kicking performance in football players - van den Tillaar, R.; Fuglstad, P. (Journal of Motor Behavior, 2017)
The authors' purpose was to investigate if there is a speed accuracy trade-off in soccer kicking by using instructions prioritizing velocity, accuracy, or both upon soccer kicking performance and kicking direction in experienced soccer players. In addition, kinematics were measured to investigate the eventual differences in performance. Thirteen experienced male footballers performed penalty kicks with different instructions prioritizing velocity, accuracy or both. Three-dimensional kinematics, together with maximal ball velocity and hitting accuracy, were measured on all kicks. The main findings were that when the main aim was accuracy, accuracy increased, while the velocity reduced, which supports Fitts' law (Fitts, 1954 Fitts, P. M. (1954). The information capacity of the human motor system in controlling the amplitude of movement. Journal of Experimental Psychology, 47, 381-391.[Crossref], [PubMed], [Google Scholar]). In addition, kicking accuracy was higher when kicking to the contralateral side. The slower ball velocity was caused by lower segmental and in run velocities. These lower segmental velocities were mainly caused by the lower maximal knee extension and pelvis rotation during the accuracy priority kicks. ABSTRACT FROM AUTHOR